WASTE MANAGEMENT IN THE ENVIRONMENTAL MANAGEMENT SYSTEM (World of finance, 2024)
Introduction. The process of waste disposal today is associated with increasing operational costs, including the costs associated with the collection, transportation and processing of waste. The main factors contributing to these high costs are fuel prices, labor costs and maintenance costs. As a result, the waste management process operates in complex and unstable conditions, which is reflected in waste disposal, recycling and environmental protection. This actualizes the scientific study of waste management in the environmental management system, because a passive reaction to the problem threatens with high costs in the production cycle in future periods.The purpose of the article is to analyse the structural elements of waste management, research into the structure of waste generation and sources of their origin, outline the proposals for the possibility of combining waste management strategies in the environmental management system.Results. The constituent elements of waste management are considered, in particular, strategic planning; prevention of environmental pollution and conservation of resources; minimization of the amount and toxicity of waste generation; choosing the best prevention option, taking into account the legislation; assessment of effects and consequences; decision-making. The structure of waste generation and sources of their origin were studied through the division into renewable and non-renewable materials, carbon-neutral biomass and non-renewable biomass. Proposals for organizations regarding the possibility of combining waste management strategies in the environmental management system are outlined.Prospects. The subject of further scientific research is the problem the electronic waste growth in the system of waste management in developing countries. This problem will be relevant, because waste processing companies in developed countries are faced with strict regimes of environmental regulation and the growing cost of waste disposal, and therefore the export of e-waste to developing countries is more economically profitable than processing in their own countries, which exacerbates the existing problem.